Age-Dependent Risks of Incidence and Mortality of COVID-19 in Hubei Province and Other Parts of China - Li, Hongdou; Wang, Shuang; Zhong, Fan; Bao, Wuyin; Li, Yipeng; Liu, Lei; Wang, Hongyan; He, Yungang (Frontiers in Medicine, 2020)
The new coronavirus SARS-CoV-2 pandemic of early 2020 poses an enormous challenge to global public health. Coronavirus Disease 2019 (COVID-19) caused by the virus has spread rapidly throughout the world, taking thousands of lives in just over two months. It is critical to refine the incidence and mortality risks of COVID-19 for the effective management of the general public and patients during the outbreak. In this report, we investigate the incidence and mortality risks of the infection by analyzing the age composition of 5319 infected patients, 76 fatal cases, and 1,144,648 individuals of the general public in China. Our results show a relatively low incidence risk for young people but a very high mortality risk for seniors. Notably, mortality risk could be as high as 0.48 for people older than 80 years. Furthermore, our study suggests that a good medical service can effectively reduce the mortality rate of the viral infection to 1% or less.